A quantum dot-silica composite as an efficient spectral converter in a luminescent down-shifting layer of organic photovoltaic devices. (20th November 2019) - Lim, Hong Chul; Koo, Ja-Jung; Kim, Jae Il; Lee, Jin-Kyu; Kim, Zee Hwan; Hong, Jong-In
Abstract : The power conversion efficiency of organic photovoltaic (OPV) devices with a luminescent down-shifting layer was enhanced by 8.9% compared to pristine OPV devices. Abstract : We developed a gradient quantum dot (QD)@polyvinylpyrrolidone (PVP)-silica composite as a spectral converter to improve light harvesting of the photoactive layer in organic photovoltaic (OPV) devices. The spectral converter prepared by a simple sol–gel method served as a luminescent down-shifting (LDS) layer that absorbed ultraviolet and emitted visible light. Re-emitted light energy from the LDS layer appeared within the absorption range of the photoactive donor material of P3HT in the OPV devices. We investigated how the light harvesting ability was affected by the concentration of QD@PVP and the thickness of the LDS layer. The OPV devices with the LDS layer showed increased power conversion efficiency (PCE) from 3.38% to 3.68% compared to pristine OPV devices due to improved incident light transmittance and increased light harvesting.